Economic Crises and Mortality Among the Elderly: Evidence from Two Russian Crises - Margarita Khvan; Elizaveta Smorodenkova; Evgeny Yakovlev (Institute of Labor Economics (IZA), 2020)
We assess the short-term effects of the two recent economic crises, the Great Recession and the collapse of the USSR, on the elderly mortality in Russia. According to our study, crises have led to an increase in mortality with quantitatively similar elasticities of death with respect to GDP fall for both events. Further analysis of the Great Recession suggests that income depreciation, limited access to medical services, and an increase in alcohol consumption are responsible for the rise in mortality. While increases at a higher rate compared to overall mortality, alcohol-related mortality explains a relatively small part of total mortality rise.
Keywords: J1; H1; I1; 330; mortality; crises